AN ANALSYSIS REALITY OF GENDER INEQUETY WOMEN BALI IN THE NOVEL “TEMPURUNG” BY OKA RUSMINI - Yayu Wahyuni Hidayat; Tuti Kartika; Enung Nurhayati (JLER (Journal of Language Education Research), 2020)
One point of view of the study of literary feminism is describing the forms of gender injustice that afflict female leaders. In this case, Sara Mills looks at the position of the figures displayed and focuses on how the readers and writers are in the text. Factors that led to gender injustice towards Balinese female figures, as well as forms of resistance to gender injustice carried out by Balinese female figures in the novel Tempurung by Oka Rusmini. This paper is a qualitative descriptive form. The subject of this analysis is the Tempurung novel by Oka Rusmini. Discourse analysis focused on gender injustice that afflicted Balinese female figures studied using biographical criticism and historical feminist literature. Data is obtained from reading techniques and note taking techniques. Data is analyzed through qualitative descriptive analysis techniques. The results showed: (1) The position of the subject-objects from the characterization of the novel "Tempurung" as a manifestation of gender injustice towards Balinese women in the form of violence (psychological violence and sexual violence), infidelity carried out by male figures, and stereotyping or negative labeling ; (2) the factors that cause gender injustice that afflict Balinese female figures in the Tempurung novel include cultural factors, and caste factors (3) criticisms of the sociohistorical approach underlying the author, which raises Balinese female figures in the Tempurung novel by becoming female independent, against adat, and refusing matchmaking.